A Climatology of the Marine Atmospheric Boundary Layer Over the Southern Ocean From Four Field Campaigns During 2016–2018. Issue 20 (14th October 2020) - Truong, S. C. H.; Huang, Y.; Lang, F.; Messmer, M.; Simmonds, I.; Siems, S. T.; Manton, M. J.
Abstract: A climatology of the marine atmospheric boundary layer (MABL) and the lower free troposphere over the Southern Ocean (SO) is constructed using 2, 186 high‐resolution atmospheric soundings from four recent campaigns conducted in the period of 2016–2018. Relationships between the synoptic meteorology and MABL thermodynamic structure are examined using a k ‐means cluster analysis, complemented by front and cyclone composite analyses. Seven distinct clusters are identified, five of which are consistent with an established climatology over the SO storm track. Two new clusters (C1 and C2) are introduced over the high‐latitude SO. C1 is commonly located poleward of the ocean polar front near mesocyclones, while C2 is located along the Antarctic coastline. A multilayer cloud structure is frequently present in clusters in the vicinity of fronts and cyclones, while a single‐layer coverage is more common in a suppressed environment, particularly at lower latitudes. A cloud‐free, multilevel inversion is frequently observed in cluster C2, possibly linked to the descending, dry, katabatic winds off the Antarctic coast. A strong, primary inversion is typically present in clusters at lower latitudes with high mean sea level pressure. Across the SO storm track and higher latitudes (cluster C1), a multilevel inversion structure is also commonly observed. A preliminary analysis of two case studies suggests that upper level advection and detrainment of convection associated with mesocyclones are potential drivers of the multilayer cloud coverage over the high‐latitude SO rather than the decoupling mechanisms common in the subtropics. Key Points: A climatology of the marine atmospheric boundary layer over the Southern Ocean is developed from four recent field campaigns A multilayer cloud structure is frequently observed in the vicinity of fronts and cyclones, particularly over the high latitudes The upper level advection and detrainment of convection associated with mesocyclones are potential drivers of the multilayer cloud coverage